Reconstruction of the Tax Court's Function as a Repressive Legal Instrument in Achieving Justice: Urgency and Future Arrangements - Utami, Antin Ekaningtyas Widhar; Sudharma, Kadek Januarsa Adi; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
Tax courts, as part of the judiciary, play a crucial role in achieving justice in society. This research aims to analyze the reconstruction of the tax court's function as a repressive legal instrument in achieving justice, with an emphasis on the urgency and future regulations related to the tax court. This research is normative legal research with a conceptual and legislative approach. The research findings confirm that the urgency of strengthening the position of the Tax Court as a repressive legal instrument is crucial in achieving social justice. This is because the court plays a strategic role as a corrective mechanism that balances government power in tax management, which often has the potential to deviate and harm taxpayers. This aligns with Philipus M. Hadjon's theory of repressive legal protection, where the Tax Court is the final line of defense ensuring the independent and objective enforcement of the rule of law, providing legal space for taxpayers to defend their rights thru objection, appeal, and lawsuit procedures. Therefore, future arrangements to strengthen the position of the Tax Court can be realized thru a comprehensive revision of Law Number 14 of 2002, which integrates the general principles of good governance (GPG) such as the principles of legal certainty, justice, transparency, professionalism, and proportionality, as well as specific principles in tax law. Affirming the finality of decisions and limiting legal remedies, as well as strengthening the principles of non-discrimination and protecting taxpayers' rights, are also important aspects of the revision to create legal certainty and justice.